Relationship between oviposition, virulence gene expression and parasitism success in Cotesia typhae nov. sp. parasitoid strains - R. Benoist; C. Chantre; C. Capdevielle-Dulac; M. Bodet; F. Mougel; P. A. Calatayud; S. Dupas; E. Huguet; R. Jeannette; J. Obonyo; C. Odorico; J. F. Silvain; et al. (Genetica, 2017)

The Cotesia sesamiae story: insight into host-range evolution in a Hymenoptera parasitoid and implication for its use in biological control programs - L. Kaiser; S. Dupas; A. Branca; E. A. Herniou; C. W. Clarke; C. Capdevielle Dulac; J. Obonyo; R. Benoist; J. Gauthier; P. A. Calatayud; J. F. Silvain; B. P. Le Ru (Genetica, 2017)

Reconstructing the invasion and the demographic history of the yellow-legged hornet, Vespa velutina, in Europe - M. Arca; F. Mougel; T. Guillemaud; S. Dupas; Q. Rome; A. Perrard; F. Muller; A. Fossoud; C. Capdevielle-Dulac; M. Torres-Leguizamon; X. X. Chen; J. L. Tan; et al. (Biological Invasions, 2015)

Phylogeography in continuous space: coupling species distribution models and circuit theory to assess the effect of contiguous migration at different climatic periods on genetic differentiation in B usseola fusca ( L epidoptera: N octuidae) - S. Dupas; B. le Ru; A. Branca; N. Faure; G. Gigot; P. Campagne; M. Sezonlin; R. Ndemah; G. Ong'amo; P.‐A. Calatayud; J.‐F. Silvain (Molecular Ecology, 2014)
Current population genetic models fail to cope with genetic differentiation for species with large, contiguous and heterogeneous distribution. We show that in such a case, genetic differentiation can be predicted at equilibrium by circuit theory, where conductance corresponds to abundance in species distribution models ( SDM s). Circuit‐ SDM approach was used for the phylogeographic study of the lepidopteran cereal stemborer B usseola fusca F üller ( N octuidae) across sub‐ S aharan A frica. Species abundance was surveyed across its distribution range. SDM s were optimized and selected by cross‐validation. Relationship between observed matrices of genetic differentiation between individuals, and between matrices of resistance distance was assessed through Mantel tests and redundancy discriminant analyses ( RDA s). A total of 628 individuals from 130 localities in 17 countries were genotyped at seven microsatellite loci. Six population clusters were found based on a B ayesian analysis. The eastern margin of D ahomey gap between E ast and W est A frica was the main factor of genetic differentiation. The SDM projections at present, last interglacial and last glacial maximum periods were used for the estimation of circuit resistance between locations of genotyped individuals. For all periods of time, when using either all individuals or only E ast A frican individuals, partial M antel r and RDA conditioning on geographic distance were found significant. Under future projections (year 2080), partial r and RDA significance were different. From this study, it is concluded that analytical solutions provided by circuit theory are useful for the evolutionary management of populations and for phylogeographic analysis when coalescence times are not accessible by approximate B ayesian simulations.

Inferring native range and invasion scenarios with mitochondrial DNA: the case of T. solanivora successive north–south step-wise introductions across Central and South America - M. Torres-Leguizamón; S. Dupas; D. Dardon; Y. Gómez; L. Niño; A. Carnero; A. Padilla; I. Merlin; A. Fossoud; J.-L. Zeddam; X. Lery; C. Capdevielle-Dulac; et al. (Biological Invasions, 2011)

Genetic bottleneck in invasive species: the potato tuber moth adds to the list - N. Puillandre; S. Dupas; O. Dangles; J.-L. Zeddam; C. Capdevielle-Dulac; K. Barbin; M. Torres-Leguizamon; J.-F. Silvain (Biological Invasions, 2008)

Phylogeography and population genetics of the maize stalk borer Busseola fusca (Lepidoptera, Noctuidae) in sub‐Saharan Africa - M. SEZONLIN; S. DUPAS; B. LE RÜ; P. LE GALL; P. MOYAL; P.‐A. CALATAYUD; I. GIFFARD; N. FAURE; J.‐F. SILVAIN (Molecular Ecology, 2006)
The population genetics and phylogeography of African phytophagous insects have received little attention. Some, such as the maize stalk borer Busseola fusca , display significant geographic differences in ecological preferences that may be congruent with patterns of molecular variation. To test this, we collected 307 individuals of this species from maize and cultivated sorghum at 52 localities in West, Central and East Africa during the growing season. For all collected individuals, we sequenced a fragment of the mitochondrial cytochrome b . We tested hypotheses concerning the history and demographic structure of this species. Phylogenetic analyses and nested clade phylogeographic analyses (NCPA) separated the populations into three mitochondrial clades, one from West Africa, and two — Kenya I and Kenya II — from East and Central Africa. The similar nucleotide divergence between clades and nucleotide diversity within clades suggest that they became isolated at about the same time in three different refuges in sub‐Saharan Africa and have similar demographic histories. The results of mismatch distribution analyses were consistent with the demographic expansion of these clades. Analysis of molecular variance ( amova ) indicated a high level of geographic differentiation at different hierarchical levels. NCPA suggested that the observed distribution of haplotypes at several hierarchical levels within the three major clades is best accounted for by restricted gene flow with isolation by distance. The domestication of sorghum and the introduction of maize in Africa had no visible effect on the geographic patterns observed in the B . fusca mitochondrial genome.

Two non-linked genes for specific virulence of Leptopilina boulardi against Drosophila melanogaster and D. yakuba - S. Dupas; Y. Carton (Evolutionary Ecology, 1999)